HIV incidence and risk factors for seroconversion among female sex workers and single mothers in a 10-year prospective cohort - Malama, Kalonde; Parker, Rachel; Wall, Kristin M; Kilembe, William; Kabengele, Chishiba; Mwangelwa, Sepo; Sharkey, Tyronza; Inambao, Mubiana; Musale, Vernon; Himukumbwa, Constance; Price, Matt A; Hunter, Eric; et al. (AIDS (London), 2025)
To compare HIV incidence among female sex workers (FSW) and single mothers, and to determine the factors associated with seroconversion among both populations. Prospective cohort conducted in Lusaka and Ndola, Zambia between 2012 and 2022. Study staff recruited FSW from common sex work locales and recruited single mothers from postnatal infant vaccination clinics. Enrolled participants were HIV-negative, aged 18-45, and identified as either a FSW or single mother. We measured HIV incidence and assessed associated factors using Poisson regression with adjusted rate ratios (aRRs) and 95% confidence intervals (CIs). The study enrolled 2,539 women (1,533 FSW and 1,006 single mothers). HIV incidence was not statistically different for FSW (3.24 per 100 person-years;95%CI:2.63-3.95) and single mothers (2.64 per 100 person-years;95%CI:2.00-3.43). Factors associated with HIV seroconversion were positive syphilis (aRR:2.03;95%CI:1.46-2.83) and trichomonas (aRR:1.48;95%CI:1.06-2.06) diagnoses, inconsistent condom use (aRR:1.60;95%CI:1.06-2.40), and greater than 6months follow-up time in the study (aRR:2.45;95%CI:1.52-3.94). Single mothers share similar HIV risk to FSW, and both populations require targeted interventions. For single mothers, government postnatal clinics should combine comprehensive sexual education with screening and treatment for syphilis and trichomoniasis. For FSW, we recommend integrated and accessible interventions to prevent HIV and sexually transmitted infections. Future studies should investigate the social determinants of condom use among both FSW and single mothers.